1996
DOI: 10.1007/bf00663010
|View full text |Cite
|
Sign up to set email alerts
|

C-kit receptor (CD0117) expression in acute leukemia

Abstract: The murine monoclonal antibody YB5.B8 (CD117) identifies a transmembrane tyrosine kinase receptor encoded by the human c-kit proto-oncogene. In this study we investigated the expression of c-kit on different types of acute leukemia to determine the degree of specificity and sensitivity of this marker for the myeloid and lymphoid lineages. C-kit was positive in over half of the 115 cases of acute leukemia studied. Overall, two thirds of AML cases expressed c-kit, whereas only one of 23 ALL patients was c-kit po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…C-kit expression appears to be a rare event in lymphoblastic leukemia of B-lineage, however. 39 Valverde et al, 47 found only one of 23 ALL cells of different types positive for c-kit expression and Morita et al 48 found no c-kit expression in 44 lymphoid blast preparations from pediatric leukemia patients and 20 cell lines of erythroid and lymphoid lineages. Whether c-kit is biologically active by transducing a growth signal in the T-lymphoblastic cells was not studied by these investigators.…”
Section: Discussionmentioning
confidence: 99%
“…C-kit expression appears to be a rare event in lymphoblastic leukemia of B-lineage, however. 39 Valverde et al, 47 found only one of 23 ALL cells of different types positive for c-kit expression and Morita et al 48 found no c-kit expression in 44 lymphoid blast preparations from pediatric leukemia patients and 20 cell lines of erythroid and lymphoid lineages. Whether c-kit is biologically active by transducing a growth signal in the T-lymphoblastic cells was not studied by these investigators.…”
Section: Discussionmentioning
confidence: 99%
“…The human stem cell factor (SCF) receptor c-KIT (CD 117) is expressed on the majority of AML blast cells whereas it is missing on acute lymphatic leukemia (ALL) cells [107]. It can easily be detected by flow cytometry and thus has become an important diagnostic tool in the differential diagnosis of AML and ALL.…”
Section: Genetic Abnormalities In Upstream Receptorsmentioning
confidence: 99%
“…A higher frequency of nonsilent genetic changes has been demonstrated in a selected group of tested AML-CBF leukemia patients. Expression of KIT was indicated only in 6.3% of ALL, which corresponds to reports of other authors [27,28,29]. …”
Section: Discussionmentioning
confidence: 52%